2020
DOI: 10.21203/rs.3.rs-17942/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Renal Involvement In Primary Sjögren’s Syndrome: Data From The Spanish Sjögrenser Cohort.

Abstract: Objectives To investigate the prevalence, associated factors, and effects of primary renal disease on morbidity in patients with primary Sjögren’s syndrome (pSS).Methods All patients in the SJÖGRENSER (registry of adult SSp patients of the Spanish Society of Rheumatology) cohort were retrospectively investigated for the presence of clinically significant renal involvement directly related to pSS activity.Results Of the 437 patients investigated, 39 (9%) presented overt renal involvement during follow-up. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The study proposed the idea that there may be a relationship between hospitalization and the presence of vasculitis, short disease duration, glomerulonephritis, neurological involvement, hepatic involvement, and hyper viscosity [ 10 ]. It was also reported that hospitalization was encountered among pSS patients with renal involvement [ 25 ]. In our study, the prevalence of extra-glandular involvement, pulmonary involvement, or urinary system involvement was higher in the patients who were hospitalized (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study proposed the idea that there may be a relationship between hospitalization and the presence of vasculitis, short disease duration, glomerulonephritis, neurological involvement, hepatic involvement, and hyper viscosity [ 10 ]. It was also reported that hospitalization was encountered among pSS patients with renal involvement [ 25 ]. In our study, the prevalence of extra-glandular involvement, pulmonary involvement, or urinary system involvement was higher in the patients who were hospitalized (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of ESRD did not increase in patients in comparison to non-SS controls, a significantly increased risk of long-term CKD was observed in SS patients, in particular in females. Similarly, a retrospective analysis of 437 patients included in the Spanish Sjögrenser registry, showed that CKD develops in about 60% of patients, thus suggesting the importance of regular monitoring for renal complications in patients with SS (84) . Finally, articular and digestive tract involvement in SS patients have been recently investigated.…”
Section: S-8mentioning
confidence: 99%
“…Frontiers in Molecular Biosciences frontiersin.org Discussion Primary Sjogren's syndrome is among the most common autoimmune diseases, affecting about 0.1-0.4% of the general population, especially in women, with a prevalence comparable to that of rheumatoid arthritis (Voulgarelis and Tzioufas, 2010). In addition to the most common salivary and lacrimal gland involvement, pSS may affect several organs, including the lungs, heart, liver, nervous system, kidneys, and joints, thus severely reducing the patients' quality of life (Bak et al, 2017;Narvaez et al, 2020;Zhao et al, 2020). Metabolomics, as an emerging strategy, is an effective method for detecting and monitoring various diseases.…”
Section: Figurementioning
confidence: 99%